Dinamika Ijtihad dalam Pengembangan Hukum Tata Negara Islam Kontomperer - Andi Muhammad Ridwan Baso Bella; Ahmad Zulkarnaen; Muhammad Naufal Wijaya; Kurniati Kurniati (Indo Publishing, 2026)
Contemporary Islamic constitutional law faces increasingly urgent pressure amid the acceleration of social, economic, and technological change, particularly in Indonesia which has the world's largest Muslim population with 86.9% of a total of 270 million people based on the 2020 BPS census, a demographic reality that renders Islamic constitutional law renewal not merely an academic discourse but an urgent practical necessity. This study aims to examine the dynamics of ijtihad in the development of contemporary Islamic constitutional law by addressing three main questions, namely the position of ijtihad as an instrument of Islamic constitutional law renewal, the methods of ijtihad used in formulating such renewal, and the contribution of ijtihad in driving Islamic constitutional law reform on a sustained basis. This study employs a normative legal research method with a library-based approach built upon three philosophical foundations, namely ontological which views Islamic constitutional law as a living and evolving normative system, epistemological which integrates the ushul fiqh approach with siyasah dusturiyah, and axiological which is oriented toward the value of public benefit as the highest goal of legal renewal. The findings affirm that ijtihad holds a position as a vital instrument that is both structural and functional in nature with constitutional legitimacy through Pancasila and Article 29 of the 1945 Constitution, operating through three primary methods namely maslahah mursalah, qiyas, and the maqasid al-shariah approach synergistically where maqasid al-shariah proves most relevant as it can reach the entire spectrum of modern constitutional issues, and contributing multidimensionally through the normative dimension that dismantles the rigidity of taqlid, the integrative dimension that reconciles sharia with the modern constitution, and the transformative dimension that converts religious values into binding public policy, as evidenced by the enactment of sharia-based legislation such as the Marriage Law, Religious Court Law, and Islamic Banking Law, while simultaneously reconciling divine sovereignty with popular sovereignty within the framework of a modern, democratic, and just constitution.